Imaging intracranial arterial patency and intravenous thrombolysis in acute ischaemic stroke - Mair, Grant (The University of Edinburgh, 2017)
Among patients presenting acutely with ischaemic stroke who are being considered for intravenous thrombolysis, prompt brain imaging is used to exclude contraindications to treatment (chiefly haemorrhagic stroke or other conditions mimicking stroke) rather than to identify which patients are more or less likely to benefit from thrombolysis. For example, it is unclear whether the presence or absence of arterial obstruction on imaging should be used to guide thrombolysis treatment decisions. In this thesis I explore methods of imaging arterial patency among patients presenting acutely with ischaemic stroke and look for associations between these early imaging findings, response to intravenous thrombolysis and functional outcome six-months after stroke onset. I primarily use data from the Third International Stroke Trial (IST-3), the largest ever randomised-controlled trial testing the use of intravenous alteplase for the acute treatment of ischaemic stroke. I begin by summarising the main features of stroke, covering techniques for imaging the brain and for imaging arterial patency, and post-stroke outcomes. Next I describe two literature reviews which I compiled to increase my understanding of the topic with particular reference to imaging arterial patency. This is followed by a summary of IST-3. Then I describe the general methods I used to address my thesis aims exploring relationships between imaging characteristics of arterial patency, treatment with intravenous alteplase and functional outcome after ischaemic stroke. Specifically, I investigated the following imaging features: - The hyperattenuating artery sign (HAS), which is a non-contrast enhanced CT finding thought to be indicative of acute arterial obstruction by thrombus or embolus - Arterial patency or obstruction as demonstrated using contrast enhanced CT and MR angiographic imaging. In addition to providing better characterisation of the HAS and a better understanding of how angiography helps to assess ischaemic stroke patients, I found that arterial obstruction (however this is identified on imaging) is associated with more severe stroke at baseline and worse functional outcome six months after stroke. I also prove that intravenous alteplase is effective in the presence of arterial obstruction, counter to a widely held concern that it may not be effective in this context. Most of my work has been published in peer reviewed journals. My work should give front line clinicians greater confidence to use intravenous alteplase for the treatment of ischaemic stroke associated with arterial obstruction on imaging, but more work is needed to better understand the implications of apparently normal arterial patency on imaging among patients with ischaemic stroke.
Keywords: ischaemic stroke; imaging; thrombolysis